Inorganic–organic hybrid polymer with multiple redox for high-density data storage - Hu, Benlin (2018)
Although organic multilevel resistance memories have attracted much attention for potential realization of the exponentially-increasing density of data storage, the ambiguous structure–property relationship and the unclear switching mechanism impeded further development of multilevel resistance memory devices. Therefore, it is very urgent to ingeniously design multilevel memory materials with a certain switching mechanism. In this contribution, we have employed a multi-redox (multiple barriers) polyoxometalate-based inorganic–organic hybrid polymer (whose effective carriers are electrically controllable) to realize a ternary resistance switching memory (multilevel memories). We do believe that the as-designed inorganic–organic polymer can integrate the multi-redox states of the POM and the processability of flexible polymers together. The as-fabricated multilevel memory devices exhibit rewriteable switching properties among three redox states by applying different RESET voltages, good endurance with distinct operation windows, and long retention. Our results could provide a new strategy to design controllable multilevel resistance memories with excellent performance.